Application of gradual incremental protocol of febuxostat for gout complicated with chronic kidney disease - Yuan Hai; Shen Min-ning; Wei Xiao-fei (Linchuang shenzangbing zazhi)
Objective To explore the application of gradual incremental protocol of febuxostat plus colchicine in reducing serum uric acid and preventing attack in gout complicated with chronic kidney disease（CKD）.Methods Ninety cases of acute gout with CKD3-4 were divided into three groups（n=30 each）.Group A received febuxostat（20-40 mg/d）,group B febuxostat（40 mg/d）plus colchicine（0.5 mg/every other day）and group C febuxostat（40 mg/d）.Frequency of gout attack, serum uric acid（UA）,glomerular filtration rate（eGFR）and proteinuria were observed before and after treatment and the incidence of adverse reactions was recorded.Results Among three groups, group C group had the most frequent attacks while groups A and B were relatively close.As compared with pre-treatment, serum UA levels of three groups at Month 1/2/3 were significantly lower than those pre-treatment（P<0.05）.At Month 3,serum UA level was higher in group A than that in group B/C and the difference was significant（P<0.05）.As compared with pre-treatment, serum creatinine levels of three groups showed a downward trend post-treatment.Serum creatinine level at Month 3 post-treatment was significantly lower than that pre-treatment（P<0.05）.As compared with pre-treatment, serum creatinine level was lower in group B than that in group A/C at Month 3.As compared with pre-treatment, eGFR levels of three groups showed an upward trend.Serum eGFR of three groups at Month 3 post-treatment was significantly higher than that pre-treatment（P<0.05）.The level of eGFR was similar in group B at Month 3 post-treatment（P>0.05）.However, increase was higher in group A than that in group B.As compared with pre-treatment, proteinuria of group A/C declined after treatment, but worsened in group B.As compared with pre-treatment, urinary protein level of group A/C decreased markedly at Month 3 post-treatment（P<0.05）and increased in group B.No serious adverse reactions occurred among three groups during treatment.Four cases of mild diarrhea occurred in group B.The incidence of adverse reactions was slightly higher in group B than that in group A/C.However, no significant difference existed between two groups（P>0.05）.Conclusion For gout complicated with CKD,gradual incremental protocol of febuxostat can effectively reduce acute attack with a significant clinical efficacy.It offers marked renal protection and fewer adverse reactions.